An investigation of accuracy and response time regarding processing mechanism of English relative clauses in EFL contexts - Navid Nasrollahi Shahri; Masoud Motamedynia; Mohammad Ghazanfari (Studies in English Language and Education, 2020)
Sentence comprehension in EFL (English as a Foreign Language) contexts is influenced by many factors. One of the most important ones is the processing mechanism of relative clauses which can be analyzed in different frameworks by researchers. So far, a wide range of research has been conducted on the processing mechanism of relative clauses in a number of languages. The results have shown a tendency toward two major categories which have been proven to be of significance, namely subject preference and object preference. Studies conducted on native speakers of English, for instance, have demonstrated subject preference by the participants. Consequently, in this study, the researchers conducted a self-paced reading experiment employing Linger software, and the data were analyzed by using the SPSS Statistics version 25. It aims to investigate the processing mechanism of English relative clauses by Iranian EFL learners. The participants were nine males and 21 females of advanced English learners majoring in the English literature, all being native speakers of Farsi. The results indicate that that the correctness percentage of subject relative clauses, and also subject modifying ones, are significantly higher than that of object ones. The results also indicated that subject relatives were processed swifter than object relatives. Finally, the researchers discussed the reasons behind such a tendency among the participants of the experiment in terms of a number of theories and principles. The findings of this study are expected to be employed in language syllabus designing as well as in grading or sequencing of materials by educators and teaching material developers.